Caring for the family of the critically ill person: the experience of nurses - Ferreira Rodrigues Galinha de Sá, Florinda Laura (2015)
Background: Nursing care in critical situations has had significant advances when it comes to the quality of patient assistance due to a large technological investment in this area during the last few years. The critically ill patient family faces significant challenges. Nurses are the health care professionals with constant presence and with the skills to assess and intervene in response to the patient’s and family’s needs due to the relation they establish with both. Caring for the family of the critically ill patient demands that nurses posess specialized skills mainly due to the emergency context. Aim: To integrate and summarize nurse’s experience of caring for the family of the critically ill person in a critical situation.Design: Comprehensive systematic review. Methods: This paper included 9 studies from electronic databases and digital scientific national repository whose participants were nurses, working in critical care units, emergency departments and pre-hospital care, with experience in caring for families of the critically ill adults. Results: The experiences of participants in the studies show that nurses experienced difficulties in caring for the family of the critically ill person. The difficulties are associated with lack of time, lack of resources, fear of emotional connection, constant focus on the care of the critically ill person, poor education, intrapersonal conflicts and lack of awareness of the family’s needs. The main strategies used by nurses in order to care for the family of the critically ill person are: promoting the presence of family members near the patient, supporting bereaved families, communicating proper information about the patient’s condition and giving relatives the opportunity to be involved in the patient’s care. Conclusions: The studies reviewed indicate that promoting family presence is essential in order to achieve high standards of nursing care to the critically ill person. However, there are not enough studies in this area to allow us to take general conclusions and there are even fewer studies using a phenomenological approach, so it is important to produce research about the lived experience of nurses caring for the family of the critically ill person.